Study on Galloping Oscillation of Iced Twin Bundle Conductors considering the Effects of Variation of Aerodynamic and Electromagnetic Forces. (26th July 2020) - Wu, Chuan; Ye, Zhongfei; Zhang, Bo; Pan, Yong; Li, Qing; Yan, Bo
Abstract : Due to the occurrence of whole-span and subspan vibration at the same time during the galloping of the iced bundle conductors, the distance between the subconductors changes, resulting in the variation of the aerodynamic parameters for the leeward subconductors. The existing conventional studies usually only consider the whole-span galloping, ignoring the relative motion and the electromagnetic force between the subconductors. Based on considering the above two factors at the same time, a new numerical simulation method to study the galloping behaviors of the iced conductors is presented. Then, the galloping behaviors of the iced twin bundle conductors' transmission line with different current intensity, initial wind attack angle, and spacer layout are studied. The galloping oscillation behaviors include time histories of vibration displacements, mode, amplitude, frequency, motion traces, and the distance between two subconductors. The simulation results showed that the whole-span and subspan vibration appear at the same time during galloping oscillation and two subconductors may collide with each other when affected by the varying electromagnetic and aerodynamic forces. The effects of varying electromagnetic and aerodynamic forces on galloping behavior cannot be ignored. The new method presented in this work can contribute to the galloping study of the iced bundle conductors.